2013
DOI: 10.3109/13813455.2013.777078
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase activity in normal pregnancy and pregnancy associated disorders

Abstract: Adenosine deaminase (ADA) is an enzyme of purine salvage pathway and has two important isoenzymes ADA1 and ADA2. The activity of ADA has been changed in diseases characterized by altered cell-mediated immunity. It was observed that total serum ADA activity was decreased during normal pregnancy compared with non-pregnant women. However, total serum ADA activity and serum ADA2 activity was increased in hyperemesis gravidarum and pre-eclampsia in pregnant women. Less information is available regarding role of ADA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In another study, healthy pregnant women had lower serum ADA, ADA‐1 and ADA‐2 activities than that of healthy non‐pregnant women . In a similar research conducted, the total serum ADA activity was decreased during NP compared with non‐pregnant women . However, total serum ADA activity and serum ADA2 activity were observed to be elevated in hyperemesis gravidarum and pre‐eclampsia in pregnant women .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In another study, healthy pregnant women had lower serum ADA, ADA‐1 and ADA‐2 activities than that of healthy non‐pregnant women . In a similar research conducted, the total serum ADA activity was decreased during NP compared with non‐pregnant women . However, total serum ADA activity and serum ADA2 activity were observed to be elevated in hyperemesis gravidarum and pre‐eclampsia in pregnant women .…”
Section: Introductionmentioning
confidence: 76%
“…25 However, total serum ADA activity and serum ADA2 activity were observed to be elevated in hyperemesis gravidarum and pre-eclampsia in pregnant women. 25 ADA activities were elevated in gestational diabetic mellitus, 26 among human immunodeficiency virus (HIV)-infected individuals 27 and women with hyperemesis gravidarum. 28 These authors did not put into consideration other possible pathological status of pregnancy and pregnancy-associated complications.…”
Section: Ada1mentioning
confidence: 95%
“…Bottini et al have reported that there is a lower frequency of GA genotype among infertile couples and women who have recurrent miscarriages [17]. However, most studies about relation of ADA with fertility were conducted on women [9,[18][19][20].…”
Section: Discussionmentioning
confidence: 95%
“…Adenosine deaminase is present in virtually all mammalian cells; its primary function in humans is the development and maintenance of the immune system. The activity of ADA has been changed in diseases characterised by altered cell-mediated immunity [ 8 ]. Lymphocyte proliferation and differentiation requires ADA [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine deaminase activity is critical in maintaining a normal pregnancy [ 12 , 13 ]. It was observed that total serum ADA activity was decreased during normal pregnancy compared with non-pregnant women [ 8 ]. One possible explanation for decreased ADA activity in normal pregnancy is due to the increase in pregnancy-related hormones such as oestradiol and cortisol, which tend to inhibit ADA activity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%